Advancing atmospheric river forecasts into subseasonal‐to‐seasonal time scales. Issue 14 (29th July 2017) - Baggett, Cory F.; Barnes, Elizabeth A.; Maloney, Eric D.; Mundhenk, Bryan D.
Abstract: Atmospheric rivers are elongated plumes of intense moisture transport that are capable of producing extreme and impactful weather. Along the West Coast of North America, they occasionally cause considerable mayhem—delivering flooding rains during periods of heightened activity and desiccating droughts during periods of reduced activity. The intrinsic chaos of the atmosphere makes the prediction of atmospheric rivers at subseasonal‐to‐seasonal time scales (3 to 5 weeks) an inherently difficult task. We demonstrate here that the potential exists to advance forecast lead times of atmospheric rivers into subseasonal‐to‐seasonal time scales through knowledge of two of the atmosphere's most prominent oscillations, the Madden‐Julian oscillation (MJO) and the quasi‐biennial oscillation (QBO). Strong MJO and QBO activity modulates the frequency at which atmospheric rivers strike—offering an opportunity to improve subseasonal‐to‐seasonal forecast models and thereby skillfully predict atmospheric river activity up to 5 weeks in advance. Key Points: The potential exists to forecast atmospheric river (AR) activity at subseasonal‐to‐seasonal (S2S) lead times of 3–5 weeks Strong MJO and QBO activity modulates AR activity at S2S lead times Numerical weather models predict AR activity with positive skill scores that vary with the MJO and QBO but lack skill at S2S lead times Plain Language Summary: Along the west coast of North America, intense rain storms that produce extreme and impactful weather occasionally happen. These rain storms are called "atmospheric rivers." Atmospheric rivers cause considerable mayhem ‐ delivering flooding rains when they occur and desiccating droughts during their absence. Because their impacts are so extreme, it would be beneficial to have as much forewarning as possible about when and where they will occur. Unfortunately, modern‐day weather models are unable to forecast atmospheric rivers beyond two weeks in advance. However, we find that the potential exists to improve forecasts of atmospheric rivers by using knowledge of the current weather in the tropics. The weather in the tropics foretells many weeks in advance when and where atmospheric rivers will impact the west coast of North America. Our findings offer an opportunity to improve weather forecasts and thereby provide more forewarning for atmospheric rivers and their extreme impacts.